PENGARUH MODEL PEMBELAJARAN INKUIRI OLEH GURU PENDIDIKAN AGAMA KRISTEN TERHADAP KREATIVITAS BELAJAR - justini Angriani Pasaribu (IAKN Tarutung, 2019)
vAbstract: This Research aim to know the influence Model The Study Inquiry By Teacher of Christian Educationto Creativity Learn The Student, with the hypothesis there are influence which are positive and signifikanbetween Model of Study Inquiry By Teacher of Christian Education to Creativity Learn The Student. Thisresearch use the descriptive quantitative approach inferensial, with the population all student of class VIII SMPCountry 1 Siantar Narumonda amounting to 102 people by sampel amount to 46 people. Data collected with theenquette closed as much 40 item compiled by writer pursuant to variable indicator according to expert theory.Test-Drive the enquette conducted to 30 student which is non research responder, and have been tested thevalidity and reliability. Result of data analysis indicate that there are influence which are positive and signifikanbetween Model of Study Inquiry By Teacher of Christian Education to Creativity Learn The Student with thecoefficient determination ( r2) = 37,69% and test the signifikan influence obtained FcountFtable equal to26,154,040, its meaning Ho refused and Ha acceptedKeyword: Model The Study Inquiry, Creativity Learn